Big data life cycle: security issues, challenges, threat and security model - SankaramAlladi, Bhima; Srinivas Prasad, Dr (International Journal of Engineering and Technology, 2017)
Today the technologies of big data are completely bringing a vast change in the entire conventional technology discipline and itâ€™s successfully applying the required latest security design methods to state the upcoming security provocations. Big Data Architecture is a â€œDataâ€ centric architecture in which security can be included in all the levels. Data is collected from different sources and Data generation is done, the next step it undergoes is Data Processing, the next step is Data storage and the last step is Data analysis. At all the levels Data plays a vital role. It aims to give basic investigation regarding most of the security risks and Big Data provocation and bought out new provocations, complication to the conventional protective domains and also for conventional trends. This deals with the definition of big data and the characteristics that effect most of the data preservation, such as 3Vâ€™s, dynamicity. It analyses the original changes and new challenges to Data security. It also provides pitch for real time practice of security infrastructure peripherals which allows extend trusted non-local virtualized processing environment. This research focus on all levels of Big Data where and when the security services and techniques can be included to acquire accurate results.